The world is all that is the case (Amsterdam : Stichting Roma Publications, 2019)
Pictures of people reading aren't simply (or necessarily or even usually) portraits. In fact, if the default setting of the portrait involves posing for the photographer, it would be more fitting to say that a picture of someone reading is a kind of anti-portrait." Walter Benn Michaels00Photographs by Arthur Ou of artists reading Ludwig Wittgenstein's 'Tractatus Logico-Philosophicus'. With corresponding quotes from Wittgenstein and an essay by Walter Benn Michaels.
Imported from: zcat.oclc.org:210/OLUCWorldCat (Do not remove)
boek
Keywords: Ou, Arthur